Massive permafrost rock slide under a warming polythermal glacier deciphered through mechanical modeling (Bliggspitze, Austria) - F. Pfluger; S. Weber; S. Weber; J. Steinhauser; C. Zangerl; C. Fey; J. Fürst; M. Krautblatter (Earth Surface Dynamics)
Recent studies have brought to light large amounts of evidence for enhanced rock slope failure from degrading permafrost rock walls. These failures have previously been thought to be subaerial and triggered by thermal heat propagation from rising air temperatures into the exposed rock faces. However, we have neglected the fact that the dividing line between cold and warm basal states of polythermal glaciers has shifted some hundreds of meters upwards at the same time. This means that previously frozen and ice-filled fragmented rock walls under cold glaciers have suddenly and for the first time in thousands of years been exposed to (i) hydrostatic pressures, (ii) warming and degrading ice in fractures, and (iii) rock mechanical degradation in warming rocks. In this paper, we hypothesize that the transition from cold- to warm-based glaciers, a scarcely observed but widespread phenomenon, caused the massive rock slide. To challenge this hypothesis, we investigated the 3.9 to 4.3×106 m3 rock slide at Bliggspitze on 29 June 2007, which detached from a north-exposed, glacier-covered rock slope at 3200 m above sea level. We (a) have analyzed the glacier transition since 1971 using aerial photographs coincident to meteorological data; (b) compared 2013–2016 ground surface temperature measurements to infer permafrost-prone and cold glacier thermal conditions; (c) categorized springs mapped in summer 2001/2012 according to geomorphological features and mineralization; (d) performed electrical resistivity tomography subsequent to failure on the destabilized rock flank in 2009; (e) conducted rock testing in frozen and unfrozen conditions; and (f) modeled the mechanical impact of hydrostatic pressure, degradation of permafrost, and glacier retreat in a universal distinct element code (UDEC). Aerial photos indicate the existence of a cold glacier from 1971–2003 above the failure volume. On the rock face above the failure volume, ground surface temperature measurements demonstrate permafrost-favorable conditions and underpin the presence of former and present cold-based glacier compartments. Since 2003, the warming of the Northern Bliggferner Glacier has been evident in the lower and upper parts. In 2007, subsequent to the warmest January–June period in a 228-year temperature record in the area of Bliggspitze, the glacier opened massive ice crevasses above the later rock slide, causing frequent ice fall. New springs developed in the former permafrost flank, and some were strong enough to cause debris flows. The high mineralization measured at springs at a proximal distance to the failure volume indicates active-layer thaw. The inversion of electrical resistivity tomography revealed thaw that reached several decameters in depth in the collapsed rock mass 2 years after failure. The tensile strength of tested paragneiss rock samples decreased by −40 % from frozen to unfrozen states, which reflects the mechanical degradation of rock bridges under warming permafrost. In this paper, we demonstrate a new type of rock slope failure mechanism triggered by the uplift of the cold–warm dividing line in polythermal alpine glaciers, a widespread and currently under-explored phenomenon in alpine environments worldwide.